P0084DIGENIC INHERITANCE: TWO RARE CASES OF GITELMAN SYNDROME. (6th June 2020) - Anglani, Franca; Pagnin, Elisa; Bertoldi, Giovanni; Gianesello, Lisa; Rigato, Matteo; Salviati, Leonardo; Calò, Lorenzo
Abstract: Background and Aims: The clinical implementation of whole-exome sequencing (WES) as molecular diagnostic tool allows investigation of the pathogenic variants interplay in multiple genes resulting in complex spectrum of phenotypes in a same patient. The phenotypic complexity of genetic disease in patients with multiple molecular diagnoses is a challenge. The blending of two distinct disease phenotypes in a same patient may suggest an apparently new clinical phenotype, while molecular diagnoses with two overlapping disease phenotypes may result in phenotypic expansion of a single disease. We present two autosomal recessive Gitelman syndrome (GS) patients whose pathogenic variants in two different genes challenged us for clinical interpretation and therapeutic intervention. Method: Case 1: GS diagnosis at 4 years of age, severe clinical phenotype (appearance at unusual early age, hypochloremia, borderline hypomagnesemia resembling Bartter syndrome (BS), need of more complex therapy. Case 2: The diagnosis of GS was made at the age of 45 years. The patient presented classical signs of GS, with less marked metabolic alkalosis and unusual chronic renal insufficiency (CRI). Exome sequencing panel was used for mutational screening of Bartter (BS) and GS genes. Sanger sequencing and Multiplex Ligation-dependent Probe Amplification (MLPA) were also applied. Results: Case 1: We detected in the SLC12A3 gene the frameshift p.(Thr7Arfs) and the missense p.(Gly264Ala) variants, the first a known disease-causing mutation, the second associated with a severe form of GS in a patient. Another known disease-causing mutation p.(Met357Thr) was detected in the KCNJ1 gene encoding renal outer medullary K+ channel, ROMK1. It is one BS gene and was never associated with GS. The SLC12A3 p.(Gly264Ala) variant's high frequency makes it uncommon polymorphism although functional because it alters NCC activity but makes questionable its causative effect on GS phenotype. Our patient severe GS phenotype may be determined by the mutations in either SLC12A3 and KCNJ1 genes inherited respectively from mother and father. If the hypomorphic SLC12A3 variant is causative, hence the heterozygous KCNJ1 pathogenic variant might be a modifier allele responsible of the GS severe presentation. Case 2: We detected two novel variants in the SLC12A3 gene [p.(Lys894fs):p.(Pro331Leu)]. Both are pathogenic according to ACMG guidelines. Another very rare missense variant p.(Val245Met) was identified in the SLC4A1 gene, whose mutations cause distal tubular acidosis type I (dRTA). The missense mutation, never associated with dRTA, is predicted pathogenic by in silico tools. Its presence questions on phenotype interpretation: blended phenotype due to a concomitant presence of a dual molecular diagnosis? Or an expansion of a single phenotype (GS) due to the presence of a modifier gene variant? dRTA and GS have overlapping features such as hypokalemia, hypercalciuria. In the patient the less marked metabolic alkalosis, and the presence of CRF points to the latter. Conclusion: Digenic inheritance in GS was reported in only one other instance. These two cases demonstrate how our understanding of the complexity of genetic heterogeneity of rare diseases is far to be completed. It becomes essential to shed light on how combinations of variants in different genes are responsible for a disease phenotype